2012
DOI: 10.1167/iovs.11-8829
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cyclosporin A Aqueous Formulation for Dry Eye Treatment: In Vitro and In Vivo Evaluation

Abstract: PURPOSE. The aim of the present study was the in vitro and in vivo evaluation of a novel aqueous formulation based on polymeric micelles for the topical delivery of cyclosporine A for dry eye treatment. METHODS.In vitro experiments were carried out on primary rabbit corneal cells, which were characterized by immunocytochemistry using fluorescein-labeled lectin I/isolectin B4 for the endothelial cells and mouse monoclonal antibody to cytokeratin 3þ12 for the epithelial ones. Living cells were incubated for 1 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…was also shown to have adequate penetration. Using Schirmer testing and osmolarity measurements, they demonstrated no altering effects on ocular surface properties [75]. Another study by Khan et al using nanoparticle suspensions reported that CsA aqueous-based solutions may even be less irritating to the eye than lipophilic emulsions [74].…”
Section: Translational Prospectsmentioning
confidence: 99%
“…was also shown to have adequate penetration. Using Schirmer testing and osmolarity measurements, they demonstrated no altering effects on ocular surface properties [75]. Another study by Khan et al using nanoparticle suspensions reported that CsA aqueous-based solutions may even be less irritating to the eye than lipophilic emulsions [74].…”
Section: Translational Prospectsmentioning
confidence: 99%
“…The first CsA formulations were oily, yielding low CsA bioavailability due to the preferential attraction of the drug to the lipophilic carrier rather than to the hydrophilic target tissue [123,124,125]. The first and only US FDA approved and commercially available formulation Restasis ® is a 0.05% CsA oil-in-water emulsion that does not deliver CsA to the corneal tissue [126]. Alternative formulations are the polymeric MPEG-hexPLA/CsA micelles [118,119,122], the cationic oil-in-water nanoemulsions leading to approximately 350 ng CsA /g cornea, 3 h after a single instillation [127,128,129] and the nonionic micelles of Solutol HS15 (poly oxyethylene esters of 12-hydroxystearic acid) with low toxicity in vivo [130].…”
Section: Novel Formulations For Peptides and The Cyclosporin Casementioning
confidence: 99%
“…We selected rabbits because numerous similarities exist between the rabbit and human ocular and nasal immune system in both homeostasis and inflammatory diseases 34,36,91,93,125,161170 : (1) several immune-mediated ocular surface diseases, including inflammatory DED are similar in rabbits and humans 91,93,170,171 ; (2) rabbit conjunctiva-associated lymphoid tissues (CALT) closely resemble the human CALT 172175 ; (3) similar to humans, rabbit palpebral conjunctiva contains an abundance of conjunctival lymphoid follicles (CLF) 173,176 ; (4) from a practical standpoint rabbits possess relatively large conjunctival surfaces and lacrimal glands offering abundant ocular mucosal tissue for immune cell studies; (5) because of the large exposed ocular surface in rabbits compared to mice, standard DED clinical tests, such as tear breakup time and fluorescein and rose bengal staining, can be much more easily performed in rabbits; (6) for practical reasons, surgical closure of the nasolacrimal ducts (NLDs) to determine the role of NALT in inflammatory DED is much easier in rabbits than in mice 122136 ; and (7) during the past several years we have been studying the rabbit ocular mucosal immune system (OMIS). 93,95 We recently found that conjunctiva from young rabbits contains an abundance of functional T reg cells that produce anti-inflammatory cytokines, such as IL-10 and TGF-β, and suppress excessive ocular surface-resident Th1 CD4 + T-cell responses 93,177 (Figures 4 and 5).…”
Section: What Can a Rabbit Model Teach Us About The Immunopathology Omentioning
confidence: 99%
“…The word “inflammation” comes from the Latin inflammo , which means “I set alight” or “I ignite.” Currently, there is no specific immunotherapy for inflammatory DED, and patients must rely on sustained nonspecific artificial tears, anti-inflammatory steroids 32,33 or cyclosporine-based 3437 drugs (e.g. Restasis) to reduce the uncontrolled ocular surface inflammation.…”
mentioning
confidence: 99%